Comparative Pharmacokinetics of Cinobufacini Capsule and Injection by UPLC-MS/MS - Li, Ming; Qin, Yanhong; Li, Zhe; Lan, Jinshuai; Zhang, Tong; Ding, Yue (Frontiers in Pharmacology, 2022)
Cinobufacini capsule and injection are two different formulations from the same source, obtained from the extraction of the skin of Bufo bufo gargarizans Cantor, which have been approved by the Chinese State Food and Drug Administration (CFDA) for the treatment of various cancers. Our previous study has found that the cinobufacini capsule and injection exhibited different anticancer effects, but their different pharmacokinetic behaviors, which could give a cause of that, have never been reported. So a sensitive and selective method for the simultaneous quantitation of 13 compounds in the rat plasma, including bufothionine, hellebrigenin, bufalin, gamabufotalin, telocinobufagin, cinobufagin, arenobufagin, cinobufotalin, desacetylcinobufotalin, bufotalin, pseudobufarenogin, resibufogenin, and desacetylcinobufagin, was established by using the Agilent 6460 mass spectrometer equipped with an ESI ion source in a multiple-reaction monitoring (MRM) mode. Chromatographic analysis was accomplished in 6 min by using an Agilent SB-C18 column and a mobile phase consisting of 0.1% formic acid in water and acetonitrile in an optimized gradient program at a flow rate of 0.3 ml/min. The correlation coefficients (r) of all analytes ranged from 0.9967 to 0.9996, while their lower limits of quantification ranged from 0.20 to 4.84 ng/ml. The method has been fully verified and applied for the pharmacokinetic difference study of the Cinobufacini capsule and injection in rats. The results showed that nine components could be quantitated in rat plasma samples after the administration of the cinobufacini capsule, while only bufothionine, bufalin, arenobufagin, and pseudobufarenogin could be detected in the cinobufacini injection group. Their pharmacokinetic studies indicated telocinobufagin, bufalin, desacetylcinobufagin, and arenobufagin were predicted as the potential active substances of the Cinobufacini capsule, while bufothionine was considered as a major ingredient in the cinobufacini injection due to its relatively high blood drug exposure. Also, the AUC of the nine components in cinobufacini capsule groups with three different doses showed a similar trend with significant differences, and the exposure increased with the increase of the dose. The pharmacokinetic characteristics of all major ingredients in cinobufacini capsules and injection were of wide variation, which could be used to explain differences in the efficacy of the cinobufacini capsule and injection and infer the pharmacodynamic ingredients of various cinobufacini preparations.